2014
DOI: 10.5897/ajmr2014.6825
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of some fungicides and bioagents against common bean anthracnose (Colletotrichum lindemuthianum Sacc. Magnus) Briosi Cavara

Abstract: Bean anthracnose caused by Colletotrichum lindemuthianum (Sacc. & Magnus) Briosi & Cavara is one of the most devastating seed-borne diseases of common bean (Phaseolus vulgaris L.) in Ethiopia.The aim of the present investigation was to evaluate the antifungal activities of bioagents and fungicides which can be used to control bean anthracnose. Three fungicides viz., Mancozeb, Folpan and Mancolaxyl, and three bioagents viz., Trichoderma harzianum Rifai, Trichoderma viride Pers. Fr. and Pseudomonas fluorescens M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…2). These results are in agreement with Fitsum et al (2014) The results indicated that all of the treatments used in this experiment were positively increased the percentage of the seed germination, while the percentage ranged between 75-100% compared with the negative control (Pathogen alone) which shows only 52.5% seed germination (table 6). Disease management ability of various treatments under greenhouse conditions varies and superiority was shown by the tetra inoculum containing Tv+ Cc+ Bp+ Sa, treatment significantly reduced the percentage of disease incidence and severity up to 0% as compared with the negative control which shows 97.50% & 72.75% respectively (Figure 3).…”
Section: In Vitro Antagonism Assaysupporting
confidence: 91%
“…2). These results are in agreement with Fitsum et al (2014) The results indicated that all of the treatments used in this experiment were positively increased the percentage of the seed germination, while the percentage ranged between 75-100% compared with the negative control (Pathogen alone) which shows only 52.5% seed germination (table 6). Disease management ability of various treatments under greenhouse conditions varies and superiority was shown by the tetra inoculum containing Tv+ Cc+ Bp+ Sa, treatment significantly reduced the percentage of disease incidence and severity up to 0% as compared with the negative control which shows 97.50% & 72.75% respectively (Figure 3).…”
Section: In Vitro Antagonism Assaysupporting
confidence: 91%
“…Obtained results conformed with Bagade et al, (2020) who found Pseudomonas fluorescens and Bacillus subtilis were effective against anthracnose in beans. Fitsum et al (2014) revealed T. harzianum was effective against anthracnose of beans followed by P. fluorescens. Sharma et al (2021) also concluded foliar spray of Bacillus subtilis or fruit dip had the potential to control mango anthracnose disease.…”
Section: In Vitro Evaluation Of Bioagents Against C Gloeosporioidesmentioning
confidence: 99%